Multidose drug dispensing systems: a market study - Reis, Ana (2023)
This study investigates the willing to pay for a Multidose Drug Dispensing System(MDD)in pharmacies. The main aim of this study is to determine whether MDD is perceived as important in society (users or not) and their willing to pay for it. OMS concluded that increasing interventions to improve adherence to therapy may have more impact on the population’shealth than any improvement in medicaltreatment. Non-adherence is the main cause of avoidable costs for the National Healthcare System. This is an observational, cross-sectional descriptive study. Structured online questionnaire was conducted with 263 participants. It was applied a binary simple logistic regression to quantify how different the risk is between variables. From 261 respondents, 75.5%were female. The youngest respondent was 19 and the oldest 83 years old. About 40% had a BSc and about 45%of the respondents were patients. 84% refer no difficulty with medication intake and about 60% report no chronic disease. 59% refer that the service would not be useful to self, however only 6% consider the service not useful to a family member/acquaintance. About 76% of the respondents refer to be willing to pay for this service (67%would consider pay 10euros or less). Female population may present an estimated reduction of about 43% in the willing to pay compared to male population. When respondents were family members the willing to pay increase compared to when they were patients (126%). Finally, the population that recognize the importance of the service for a family member/acquaintance is expected to have anestimated increase in the willing to pay of about 190% when compared to the population that does not recognize that importance. In this study, generally, MDD service was perceived as important and men, more than women, havethe willing to pay for it.